Aspek Ekologi Dalam Kumpulan Puisi Baromban Karya Iyut Fitra - Junita, Fransiska; Iswadi Bahardur; Armet (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
his research was conducted to determine the ecological aspects of literary works contained in the collection of Baromaban poems by Iyut Fitra from the perspective of literary eco-criticism. The purpose of this study is to describe the cultural ecology depicted in Iyut Fitra's Baromban poetry collection which is described in Iyut Fitra's Baromban poetry collection. This type of research is a qualitative research with a descriptive analysis method. The data in this study are array quotes contained in the collection of Baromban poems by Iyut Fitra which contain aspects of literary ecology. The data source in this research is a collection of Baromban poems by Iyut Fitra. Based on the analysis related to the data, it can be concluded that the first three things are related to technology, production or exploitation of resources and the environment. secondly, the pattern of community action in exploiting and producing resources using the technology they have. third Patterns of behavior in society that affect other cultural aspects such as; Value systems, belief systems and religious systems.